Building intelligent cloud applications develop scalable models using serverless architectures with Azure - Harrera Garcia, Vicente; Biggs, John 1975- (O'Reilly Media, Inc., 2019)
Serverless computing is radically changing the way we build and deploy applications. With cloud providers running servers and managing machine resources, companies now can focus solely on the application's business logic and functionality. This hands-on book shows experienced programmers how to build and deploy scalable machine learning and deep learning models using serverless architectures with Microsoft Azure. You'll learn step-by-step how to code machine learning into your projects using Python and pretrained models that include tools such as image recognition, speech recognition, and classification. You'll also examine issues around deployment and continuous delivery, including scaling, security, and monitoring.